Cell Surface Hsp90- and αMβ2 Integrin-Mediated Uptake of Bacterial Flagellins to Activate Inflammasomes by Human Macrophages - Thi Xoan Hoang; Jae Young Kim (Cells, 2022)
All-trans retinoic acid (ATRA) is an active metabolite of vitamin A, which plays an important role in the immune function. Here, we demonstrated that ATRA induces the heat shock protein (Hsp) 90 complex on the surface of THP-1 macrophages, which facilitates the internalization of exogenous bacterial flagellins to activate the inflammasome response. Mass spectrometric protein identification and co-immunoprecipitation revealed that the Hsp90 homodimer interacts with both Hsp70 and αMβ2 integrin. ATRA-induced complex formation was dependent on the retinoic acid receptor (RAR)/retinoid X receptor (RXR) pathway and intracellular calcium level and was essential for triggering the internalization of bacterial flagellin, which was clathrin dependent. Notably, in this process, αMβ2 integrin was found to act as a carrier to deliver flagellin to the cytosol to activate the inflammasome, leading to caspase-1 activity and secretion of interleukin (IL)-1β. Our study provides new insights into the underlying molecular mechanism by which exogenous bacterial flagellins are delivered into host cells without a bacterial transport system, as well as the mechanism by which vitamin A contributes to enhancing the human macrophage function to detect and respond to bacterial infection.